Effect of increasing dose level of a novel consensus bacterial 6-phytase variant on phytate degradation in broilers fed diets containing varied phytate levels. Issue 3 (4th May 2022) - Dersjant-Li, Y.; Christensen, T.; Knudsen, S.; Bello, A.; Toghyani, M.; Liu, S. Y.; Selle, P. H.; Marchal, L.
ABSTRACT: 1. The effect of increasing the dose level of a novel consensus bacterial 6-phytase variant on apparent ileal digestibility (AID) of phosphorus (P), phytic acid (inositol hexa-phosphate, IP6 ) and ileal IP6 degradation profile was studied in diets containing varying phytate-P (PP) levels. 2. Ross 308, one-day-old males (n = 1, 800) were allocated to cages (20 birds/cage, six cages/treatment) in a completely randomised design employing a 3 × 5 factorial arrangement (three PP levels: 2.45 (low) 2.95 (medium) and 3.45 g/kg (high); five dose levels of phytase (PhyG): 0, 500, 1, 000, 2, 000 and 4, 000 FTU/kg). Phased diets were based on wheat, corn, soybean meal, rapeseed meal and rice bran (d 0 to 10; 2.60 g/kg digestible P, 7.6 g/kg calcium (Ca); d 11 to 21; 2.10 g/kg digestible P, 6.4 g/kg Ca). Ileal digesta was collected on d 21 for determination of P, IP6 and IP-esters content. Data were analysed by factorial ANOVA; means separation was achieved using Tukey's HSD test. 3. Increasing PP reduced AID of IP6 and sum of IP3-6 (%) (P < 0.05) but absolute P-release (g/kg diet) above NC was increased (P < 0.05) at high vs . low PP. Increasing phytase dose exponentially increased (P < 0.001) AID IP6, sum of IP3-6 (%) and digestible IP3-6 -P g/kg diet (P < 0.001). AID P was increased but there was an interaction with PP level (P < 0.001). Ileal accumulation of IP5-3 -P was universally low with PhyG at ≥1, 000 FTU/kg (<0.06 g/100 g DM). At 2, 000 and 4, 000 FTU/kg, AID IP6 was 97.2, 92.7, 92.6% and 100, 97.2, 97.1%, respectively, at low, medium and high PP. At 2, 000 FTU/kg, phytate-P release estimated as the increase (above NC) in ileal digestible sum of IP3-6 -P in the diet was 2.26, 2.59 and 3.10 g/kg in low, medium and high PP, respectively. 4. The data demonstrated that the novel phytase was effective in breaking down phytate to low IP-esters in diets with varied PP content but the optimal dose level for maximising P-release may differ in diets with varying PP content.